Responding to diversity in groups: exploring professional uses of self. Issue 3 (2nd October 2022) - LaRocque, Sarah; Popiel, Melissa; Este, David; Pelech, William; Pillay, Roshini; Nicholas, David; Kilmer, Christopher
ABSTRACT: Despite its historic prominence in group work, there is little empirical research to support our understanding of the professional use of self in group work. This paper reports the results of a SPARC endorsed study, which focused on group workers' experience and struggle with their professional uses of self in groups in responding to diversity. Using focus groups, a semi-structured interview format, and Straussian grounded theory data analysis, two key themes emerged – grappling with professional uses of self and disengagement from professional uses of self. When grappling with professional uses of self, group workers employed intentional self-disclosure, opened space, and supported norms for the expression of diversity, humility, genuineness, and reflexivity. Disengagement occurred in response to fear and often resulted in an overemphasis on group tasks. Our results suggest that the effective professional use of self in the here and now of group dynamics creates a sense of safety for both the group workers and the group members when responding to diversity. The implications of this study highlight the need for a method that supports critical self-reflection in real-time in group and builds capacity for responsibly responding to diversity in groups.